The Public Administration's Commitment to the Sustainable Development Model - Islas Gurrola, Alicia Monserrath (2026)
The paper analyzes and explains the relevance of public administration in the 2030 Agenda and the Sustainable Development Goals, as they constitute a strategy aimed at protecting the economic and social life of the planet. This strategy is based on a viable institutional framework, which requires coordinated collaboration processes through the use of appropriate management, administration, and implementation tools capable of demonstrating the ability of States to reduce environmental destruction and social inequality resulting from practices that squander humanity's common resources and assets. In this context, it is essential that administrative institutions assume their responsibility, relying on managerial and operational innovation, in order to contribute to the configuration of a new, more equitable, inclusive, and sustainable way of life.